Procurement effectiveness in Local Government Engineering Department (LGED) under IDA and GoB funded projects - Aziz, Md. Abdul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.